(untitled) (Journal of history, 2022)
Based on the materials of the settlement of the early Iron Age Abylai in Central Kazakhstan, a mass burial of complete and almost complete skeletons of domestic animals was investigated. This work is intended to present the results of the analysis carried out on these materials.The aim of the work is to determine the causes of the formation of bone accumulation. For this, an analysis was made of the composition of the elements of the skeleton, the age composition of the animals.The results of archaeozoological studies have shown that the burial of animals was a one-time. In the settlements of the early Iron Age, such a case was encountered for the first time. A comparison was made of a sample of bone remains from the pit and from the cultural layer of the settlement: by species composition, by composition of skeletal sections, by age composition. As the results of the analyzes show, these samples have significant differences. The bones from the pit are almost all intact, while those from the cultural layer have characteristics typical of household waste. According to the data obtained, at the beginning of spring, 89 small cattle and 6 cattle were buried in the pit in a short period of time. Most of the animals were skinned. The reason for the mass death of animals could be a natural disaster or an epizootic. It has been suggested that the death of livestock occurred as a result of “jute”(mass death of livestock during natural disasters in Kazakh ethnography). Key words: Central Kazakhstan, Early Iron Age, Tasmolin culture, settlement, mass death of animals.